Evaluation of leukocyte depletion of packed red blood cell units and impact on clinically observed transfusion reactions - Steblaj, Barbara; Galli, Jasmin; Torgerson, Paul; Kutter, Annette (Frontiers in Veterinary Science, 2023)
The aim of this retrospective study was to determine whether there is an association between leukoreduction of packed red blood cell (pRBC) units and reduction of clinically observed transfusion reactions (TR), particularly febrile non-haemolytic transfusion reactions (FNHTR), and better outcomes in dogs. Secondary aims were to evaluate the effects of other factors suspected to influence transfusion reaction frequency or survival, including crossmatching, use of immunosuppressive drugs and age and number of the blood products being administered.Materials and methods: Medical data on dogs transfused with leukocyte-reduced (LR) and nonleukocyte-reduced (N-LR) pRBC units at the *, *